Two-species models for the rheology of associative polymer solutions: Derivation from nonequilibrium thermodynamics - Stephanou, Pavlos S.; Tsimouri, Ioanna Ch.; Mavrantzas, Vlasis G. (My University, 2020)
We show how two-species models, already proposed for the rheology of networks of associative polymer solutions, can be derived from nonequilibrium thermodynamics using the generalized bracket formalism. The two species refer to bridges and (temporary) dangling chains, both of which are represented as dumbbells. Creation and destruction of bridges in our model are accommodated self-consistently by assuming a two-way reaction characterized by a forward and a reverse rate constant. Although the final set of evolution equations for the microstructure of the two species and the expression for the stress tensor are similar to those of earlier models based on network kinetic theory, nonequilibrium thermodynamics sets specific constraints on the form of the attachment/detachment rates appearing in these equations, which, in some cases, deviate significantly from previously reported ones. We also carry out a detailed analysis demonstrating the capability of the new model to describe various sets of rheological data for solutions of associative polymers.
Keywords: Associative polymers; Dangling chain; Evolution equations; Non equilibrium thermodynamics; Rheological data; Stress tensors; Two ways; Two-species models